Infantile Hepatic Hemangioendothelioma. A clinical case (Boletin Médico de Postgrado, 2020)
Infantile hemangioendothelioma is a rare, usually benign, disease. We present a case of a 3-month-old infant who was admitted in the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga with the diagnosis of herbaceous poisoning (peppermint) and metabolic ileus. Hepatomegaly was the most characteristic sign in clinical examination and was associated with elevated levels ​​of alpha-fetoprotein. Echographic and tomographic findings revealed multiple rounded lesions that impressed liver metastases. The patient died 23 days after admission and the postmortem diagnosis showed giant hepatic cavernous hemangioendothelioma. Diagnosis of hemangioendothelioma usually can be done without histopathological confirmation, especially in infants, when clinical, laboratory and imaging features are very suggestive of this disease, however there are exceptions as the one presented in this case.
Keywords: hepatic hemangioendothelioma; infant; diagnostic; evolution